The Effectiveness of Nutrition, Life Style and Work Place Environment in Relation to Occupational Health and Productivity - Rafique, Rimsha; Muzammil, Hafiz Shahzad; Khan, Imad Ud Din (Indus Journal of Bioscience Research, 2025)
Diet and nutrition is one of the integral components that affect the productivity of worker, their efficiency and attitude towards daily work chores. The energy levels and well-being of individuals is directly proportional to being mentally and physically present. In order to evaluate the intake of nutrients, the associated factors and their effect on workplace productivity, a across sectional study was conducted with 216 participants between age 18-55 years. In order to minimize biasness simple random sampling technique was implied. The sample population was selected from teaching and administrative staff of different private sector universities in Lahore. Time duration of the study was 6 months, from june 22, 2024 to December 22, 2024. Different aspects about their personal and workplace dynamics were questioned. A multi-dimensional questionnaire, that consisted of socio-demographic information, food frequency and workplace related queries, was used. The main questions asked included assessment of their physical activity, an overview of the food intake, challenges faced at work and how does food intake effect their workplace productivity, either they had an environment that promoted healthy lifestyle or not. Data was analyzed using SPSS version 2.O. Descriptive analysis, cross-tabs and chi-square test was used to find out the association between different factors from socio-demographics, physical activity, frequency of foods consumed and how they impact the workplace productivity, and either those associations are significant or not. Results showed significant association between breakfast venue and punctuality (p-value: 0.012), skipping breakfast and monthly leaves (p-value: 0.02), physical activity was associated with energy levels (p-value: 0.001), physical tiredness (p-value: 0.008) and hard to get work done (p-value: 0.013). BMI was significantly related to consuming one or more important meals at work (p-value: 0.001). Meanwhile tea and coffee consumption had no significant impact on energy levels at work (p-value: 0.339). Also, BMI was not related to recreational physical activity (p-value: 0.637). The overall results showed that overall health and lifestyle had an impact on productivity at work. In order to maximize the worker output, the workplace needs to be supportive of their employees maintaining personal health and well-being. Gender, living situation and breakfast related habits played a major role in food preferences and availability. Energy levels at work were also affected by a number of factors like incentives and physical activity. Either a person lived at home or hostels, also led to deteriorating eating habits which in turn affected the productivity at work.